Analisis faktor-faktor yang mempengaruhiAudit delay pada perusahaan manufaktur yangTerdaftar di bei periode 2011-2014 - Sulistyani, Sulistyani; , Dr. Noer Sasongko, SE, M.Si, Ak (2016)
The purpose of this reseach is to analyze the factors that effect audit delay to the manufacturing companies listed on the Indonesia Stock Exchange period 2011-2014. The examined factors of this research are company size, leverage, quality of a public accounting firm, and auditor's opinion as the independent variables, while audit delay as the dependent variables. Sampling technique employed in this study is the purposive sampling with the population of 142 companies, while the total sample of 56 companies. The data analysis is uses multiple regresions.The results of the study show that the company size, leverage, and quality of a public accounting firm have significant influence towards audit delay, while auditor's opinion do not have influence towards audit delay.